Kontribusi Teologis Kitab Yunus dan Aplikasinya dalam Kehidupan Orang Percaya - Christopher Alexander; Yohanes Rahdianto Suprandono (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
This article was written to discover the theological contributions of the book of Jonah and its application in the lives of believers. The book of Jonah is one of the books in the Old Testament (OT) that is no less important than the other books. Although it only contains 48 verses divided into four chapters, this book also significantly contributes to building Christian theology. The method used is a qualitative method with a literature study approach. This research concludes that there are at least three theological contributions from the Book of Jonah, namely first, God's Call to Believers, where believers are called to have a compassionate heart for those who have not been saved and who are called to proclaim the news of Salvation to them so that believers need to have a heart that is obedient and quick to fulfill God's call; Second, the concept of Salvation, where the Salvation that God offers is not only for the Israelites but also for other nations, so believers need to preach the Gospel. Third, God's Sovereignty, where the God we worship is the God who reigns over the universe and everything in it; he is also the God who cares for and accompanies His people. Therefore believers need to surrender and fully believe in God's destiny. God is carrying out His call.